La inadecuada aplicación de ENIPLA como política pública en materia de derechos sexuales y reproductivos frente a las comunidades indígenas en Ecuador - Aguilar Flores, María Paula (2017)
Interculturalism corresponding to the theories of inclusion of minorities has been regarded as a cross-cultural element to public policies in order to assure the equality in rights and obligations for individuals and different groups. In Ecuador, a country considered to be highly diversified in terms of culture, this approach was adopted by the Intersectoral Strategy for Youth Pregnancy Prevention and Family Planning (ENIPLA), acronym in Spanish, as a mechanism to deal with the heterogeneity among different nationalities and cultures in the country. Concerning indigenous communities, in order to keep their knowledge, values and community practices and to include them in governmental strategies, this approach needs to be addressed in both, normative and operational terms, last ones that in the case of ENIPLA were absent, causing the exclusion of the specificities of indigenous communities and leading to have a public policy lacking of social, cultural and linguistic relevance. This paper discussed about the components of ENIPLA in relation to the forms of organization and affective interaction of indigenous communities in Ecuador and was based on the analysis of social systems as theoretical perspective that can elucidate the importance of the interaction of different actors and thus of intercultural dialogue and exchange of ideas, to promote the inclusion of indigenous people during the Public Policy formulation process so that, public policies can be co-constructed and include ethnic variables and the diversity of concepts related to health, the body and sexuality.